Modulation of immunosuppressive cells and noncoding RNAs as immunotherapy in osteosarcoma - Xia, Yidan; Wang, Dongxu; Piao, Yuting; Chen, Minqi; Wang, Duo; Jiang, Ziping; Liu, Bin (Frontiers in Immunology, 2022)
The most common bone cancer is osteosarcoma (OS), which mostly affects children and teenagers. Early surgical resection combined with chemotherapy significantly improves the prognosis of patients with OS. Existing chemotherapies have poor efficacy in individuals with distant metastases or inoperable resection, and these patients may respond better to novel immunotherapies. Immune escape, which is mediated by immunosuppressive cells in the tumour microenvironment (TME), is a major cause of poor OS prognosis and a primary target of immunotherapy. Myeloid-derived suppressor cells, regulatory T cells, and tumour-associated macrophages are the main immunosuppressor cells, which can regulate tumorigenesis and growth on a variety of levels through the interaction in the TME. The proliferation, migration, invasion, and epithelial–mesenchymal transition of OS cells can all be impacted by the expression of non-coding RNAs (ncRNAs), which can also influence how immunosuppressive cells work and support immune suppression in TME. Interferon, checkpoint inhibitors, cancer vaccines, and engineered chimeric antigen receptor (CAR-T) T cells for OS have all been developed using information from studies on the metabolic properties of immunosuppressive cells in TME and ncRNAs in OS cells. This review summarizes the regulatory effect of ncRNAs on OS cells as well as the metabolic heterogeneity of immunosuppressive cells in the context of OS immunotherapies.